Determinants and causes of maternal mortality in Iran based on ICD-MM: a systematic review - Rostam Zalvand; Maryam Tajvar; Abolghasem Pourreza; Hadi Asheghi (BMC, 2019)
Abstract Background No systematic review has explored the causes of and factors associated with maternal mortality in the context of Iran. This study reviewed determinants and causes of maternal mortalities during pregnancy, delivery and the puerperium using the International Classification of Diseases-Maternal Mortality (ICD-MM), introduced by the World Health Organization. Methods A systematic electronic search of all the studies that identified causes and/or determinants of maternal deaths in any part of Iran or in the whole country were included, without any restriction of time or language of studies. To identify the studies to include in this study, a combination of hand searching and bibliographies was also conducted. These sources and citations yielded a total of 653 articles; nevertheless, only 29 articles met the inclusion criteria, hence, required data were extracted, summarized, and grouped together from these papers and are reported in the tables. Results Amongst the 29 studies published between 2003 and 2017 in Iran, 24 studies were cross-sectional. Overall, 4633 deaths were reviewed, and 2655 (58%) of the cases included the data on the causes of death generally. According to the ICD-MM, a total of 69.9, 20.6, and 5.2% of the mortalities were due to direct, indirect and unspecified causes respectively and 4.3% of the causes were not clear in several studies. The leading direct and indirect causes of death were identified as hemorrhage (30.7%) and hypertensive disorders (17.1%) and circulatory system diseases (8.1%) respectively. Several factors including gravidity, type of delivery, socio-economic status of mothers, locations of birth, death and maternity care venues were found in the original studies as the most important determinant of maternal mortalities in Iran. Conclusions This study, provided an updated summary of evidences on the causes and determinants of maternal death in Iran, which is critically important for the development of interventions and reduction of the burden of maternal mortality and morbidities.